2018
DOI: 10.1364/oe.26.012257
|View full text |Cite
|
Sign up to set email alerts
|

Integrated optoelectronic oscillator

Abstract: With the rapid development of the modern communication systems, radar and wireless services, microwave signal with high-frequency, high-spectral-purity and frequency tunability as well as microwave generator with light weight, compact size, power-efficient and low cost are increasingly demanded. Integrated microwave photonics (IMWP) is regarded as a prospective way to meet these demands by hybridizing the microwave circuits and the photonics circuits on chip. In this article, we propose and experimentally demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(57 citation statements)
references
References 28 publications
1
56
0
Order By: Relevance
“…The global uncertainty is ±2 dB at 2s with accredited calibration [23,24]. Recent works concur with Integrated OEO [25] with good results with resonator on chip and athermal waveguides applied to ring resonators [26].…”
Section: Realized Systemsupporting
confidence: 64%
“…The global uncertainty is ±2 dB at 2s with accredited calibration [23,24]. Recent works concur with Integrated OEO [25] with good results with resonator on chip and athermal waveguides applied to ring resonators [26].…”
Section: Realized Systemsupporting
confidence: 64%
“…This is, to the best of our knowledge, the widest tunability range reported for a Si-based OEO. A phase noise near -110 dBc/Hz at the offset frequency of 1 MHz, comparable with state-of-the-art photonic OEO 11,12 , is measured for different oscillation frequencies along the 12 GHz tuning range. Concurrently, the proposed OEO performs a precise translation of the laser-to-RR wavelength separation into the microwave domain, where it can be precisely measured.…”
Section: Introductionmentioning
confidence: 58%
“…In addition, the progress of integrated microwave photonics (IMWP) 9 provides now a solid framework for the full integration of an OEO. Several efforts in this direction have been demonstrated recently 10,11,12 . M. Merklein et al, in 10 demonstrated ultrawide frequency tunable signals up to 40 GHz by using OEO based on stimulated Brillouin scattering (SBS).…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, many achievements have been reported on the photonic integrated circuits for possible radar applications [400]. In particular, a variety of integrated optical beamformers have been demonstrated based on optical ring resonators [71], Mach-Zehnder delay interferometer [401], and arrayed waveguide grating [402]; integrated OEOs were also reported although the phase noise performance still needs improvement [403]. In addition, some multifunctional building blocks such as reflective-type microring resonator [404] and programmable 2D mesh network [405] have been demonstrated, which might be useful for reconfigurable or software-defined microwave photonic radar.…”
Section: Discussionmentioning
confidence: 99%